Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.